Fulminant cerebral edema as a lethal manifestation of COVID-19 - Antoon J.M. van den Enden, MD; Lennart van Gils, MD, PhD; Joost A.M. Labout, MD, PhD; Mathieu van der Jagt, MD, PhD; Walid Moudrous, MD (Radiology Case Reports, 2020)
The contribution of neurological symptomatology to morbidity and mortality after infection with Severe Acute Respiratory Syndrome-associated Coronavirus (SARS CoV II) is ill-defined. We hereby present a case of a 57-year old male patient, in excellent physical condition, who was admitted to the Intensive Care Unit (ICU), with respiratory distress duo to SARS CoV II-induced bilateral pneumonia. After 2 weeks at the ICU, with respiratory conditions improving, the patient developed lethal cerebral edema. This case advocates regular wake-up calls in Coronavirus disease 2019 patients for neurological (radiological) evaluation to provide rapid diagnosis and a therapeutic window for fulminant central nervous system complications.